Assessing the Antioxidant Properties, In Vitro Cytotoxicity and Antitumoral Effects of Polyphenol-Rich Perilla leaves Extracts - Gigi Adam; Florina Daniela Cojocaru; Liliana Verestiuc; Oana Cioanca; Ingrid-Andrada Vasilache; Ana-Maria Adam; Cornelia Mircea; Aurel Nechita; Valeriu Harabor; Bogdan Huzum; AnaMaria Harabor; Monica Hancianu (MDPI AG, 2023)
(1) Background: This study aimed to outline the antioxidant, antitumoral, and cytotoxic proprieties of various types of Perilla frutescens extracts obtained from the leaves of the species. (2) Methods: We determined total polyphenols, flavonoids and anthocyanins contents, as well as the in vitro antioxidant, antitumoral, and cytotoxic actions in three types of ethanolic extracts (E1, E2, E3) and in three types of acetone: ethanol extracts (A1, A2, A3) of Perilla frutescens according to standardized procedures. (3) Results: We found that Perilla frutescens ethanolic extracts had the highest total phenol and anthocyanins concentrations. The flavonoids concentration was not statistically different between the extracts. The iron chelating capacity, hydroxyl radical scavenging capacity, superoxide anion radical scavenging capacity, and lipoxygenase inhibition capacity showed a significant increase with higher concentrations of Perilla frutescens extracts, particularly the ethanolic extracts. Perillyl alcohol had greater cytotoxic capacity in the MG-63 cell line and E1 extract showed similar significant cytotoxic effects in the A431 cell line. (4) Conclusions: Both ethanolic and acetone-ethanol extracts from Perilla frutescens exhibited important antioxidant and antitumoral actions in vitro, which proportionally increased with concentration. The cytotoxic threshold determined in this study for various types of extracts could help determine the best dosage with the maximum antioxidant and antitumoral potential. Our results could serve as a basis for further studies that will investigate the cytotoxic effects of Perilla frutescens variants on various types of cancer cell lines.